Ecological performance differs between range centre and trailing edge populations of a cold-water kelp: implications for estimating net primary productivity - Nathan G. King; Pippa J. Moore; Albert Pessarrodona; Michael T. Burrows; Joanne Porter; Mathilde Bue; Dan A. Smale (Marine Biology, 2020)
Kelp forests are extensive, widely distributed and highly productive. However, despite their importance, reliable estimates of net primary productivity (NPP) are currently unknown for most species and regions. In particular, how performance and subsequent NPP change throughout a species range is lacking. Here, we attempted to resolve this by examining growth and performance of the boreal kelp, Laminaria digitata, from range centre and trailing edge regions in the United Kingdom. During the peak growth season (March/April), range-centre individuals were up to three times heavier and accumulated biomass twice as fast as their trailing-edge counterparts. This was not apparent during the reduced growth season (August/September), when populations within both regions had similar biomass profiles. In total, annual NPP estimates were considerably lower for trailing-edge (181 ± 34 g C m −2 year −1 ) compared to range-centre (344 ± 33 g C m −2 year −1 ) populations. Our first-order UK estimates of total standing stock and NPP for L. digitata suggest this species makes a significant contribution to coastal carbon cycling. Further work determining the ultimate fate of this organic matter is needed to understand the overall contribution of kelp populations to regional and global carbon cycles. Nevertheless, we highlight the need for large-scale sampling across multiple populations and latitudes to accurately evaluate kelp species’ contributions to coastal carbon cycling.

Risk management to prioritise the eradication of new and emerging invasive non-native species - Olaf Booy; Aileen C. Mill; Helen E. Roy; Alice Hiley; Niall Moore; Pete Robertson; Simon Baker; Matt Brazier; Mathilde Bue; Richard Bullock; Steve Campbell; Dominic Eyre; et al. (Biological Invasions, 2017)